The fate of Chinese refugees in post-war Indonesia, 1946–1947 - Alamsyah, Adi (Balai Pelestarian Kebudayaan Wilayah X, 2024)
This article discusses the daily lives of the Chinese community in Indonesia after the proclamation of independence. Chinese community had a very different life compared to when Indonesia was still under Dutch colonial rule. Especially when the indigenous community (Bumiputra) voiced the adage